LEGAL PROTECTION OF PARTIES IN INFORMATION TECHNOLOGY-BASED MONEY LENDING AND BORROWING SERVICE CONTRACTS OR PEER-TO-PEER LENDING - Febriansyah, Indria; Sinaga, Niru Anita (JILPR Journal Indonesia Law and Policy Review, 2025)
Legal Protection for Parties in Information Technology-Based Money Lending and Borrowing Service (LPMUBTI) or Peer-to-Peer (P2P) Lending Contracts in Indonesia. P2P Lending is a financial technology innovation that enables lenders and borrowers to transact directly without the intermediation of traditional financial institutions. Despite providing ease of access to financing, P2P Lending also presents various legal risks, such as imbalances in rights and obligations within contracts, misuse of personal data, and the proliferation of illegal platforms. This research employs a normative legal research method with a statutory approach and analyzes the regulations of the Financial Services Authority (OJK), particularly POJK Number 77/POJK.01/2016. The research findings indicate that although P2P Lending regulations are quite comprehensive, their implementation still faces various challenges, including low financial literacy among the public and weak supervision of illegal platforms. To create a fair, safe, and sustainable P2P Lending ecosystem, it is necessary to strengthen regulations, increase financial literacy, and provide more effective legal protection for lenders and borrowers. The recommendations provided include stricter law enforcement against illegal platforms, contract transparency, and education for the public regarding their rights as users of P2P Lending services.